Suzuki type fixed point theorems for generalized multi-valued mappings in b-metric spaces - Yingtaweesittikul H. (Springer Publishing Company, 2015)
In this paper, we obtained a new condition for a multi-valued mapping in a b-metric space, which guarantees the existence of its fixed point. © 2013 Yingtaweesittikul; licensee Springer.